EFISIENSI REPRODUKSI SAPI PERSILANGAN LIMOUSIN DAN PERANAKAN ONGOLE (LIMPO) DI DESA SLOROK KECAMATAN KROMENGAN KABUPATEN MALANG - Adi Andaka (AVES: Jurnal Ilmu Peternakan, 2016)
The research was held in Slorok village, Kromengan district, Malang began on 10th until 30th June 2012.The result of this research was to know the grade CR, S/C, DO, and CI in the cattle Limousin and PO cow in Slorok village, Kromengan district, Malang.The subyek of this research were the Limousin and PO cow farm in Slorok village, Kromengan district, Malang. The methode of this survey was by using scunder data that was IB note card that was provided in farm. The result of this research was 55% of CR so that the number of the conception be normal, the value of S/C was 1,7 times, the value of DO 64,,07 days, and the value of CI was 357,98 days.From the result could be concluded that the level of fertyliti the female animals in Kromengan district were good enough and had normal preserving management. The suggestion of this research was cattleman should had always completed the recording farm so that made farming management be casier